Art History, Heritage Games, and Virtual Reality - Champion, Erik; Foka, Anna (Routledge, 2020)
This chapter focuses on how the engaging and entertaining medium of virtual reality and serious games has potential to connect traditional galleries, libraries, archives, and museum sector organizations with contemporary audiences by blending old traditions and new technologies. It discusses the relevance and increasing intersecting importance of virtual heritage and serious games, especially those dealing with topics and issues in art history. Traditionally, art history has been viewed as concern about context of creation, curation, critique, and classification of art, but its range and focus is seldom agreed on. A conventional view of art history may suggest that, as field, it is dedicated to issues of classification and the development of related expertise in curation and critique. Art can, however, now contain its own “intelligence,” its own sensors and its own tools, perform functions and queries on vast scale, incorporate or reject dynamic content, and reconfigure itself according to the environment or the sensitivity of the platform that hosts it.